Technologies and Mental Health in University Students: An Unhealthy Combination - Silva, Mariana Pires Ferreira Novaes da; Cardoso, Gabriela Miloch da Silva; Priolo Filho, Sidnei Rinaldo; Weber, Silke Anna Theresa; Corrêa, Camila de Castro (International Archives of Otorhinolaryngology, 2022)
Introduction The exposure of medical students to a full-time schedule that includes classes, extracurricular activities, patients' lives responsibility, and great competition between classmates can interfere in emotional issues and in the sleep time.Objective The aim of the present study was to evaluate the sleep quality, and the incidence of anxiety and depression in medical school undergraduates as well as the relationship of these parameters with the intense use of technologies.Methods Fifty-five medical school undergraduates in their second year participated in the present study, answering questionnaires to evaluate sleep quality (Pittsburgh sleep quality index - PSQI), night-time use of technology (sleep time-related information and communication technology - STRICT), and signs of anxiety or depression (hospital anxiety and depression scale - HADS).Results The results showed 31 students (56.4%) with poor sleep quality (PSQI > 5). Based on the STRICT questionnaire, 36 (65.4%) of the participants referred to making use of technology at night-time; and 34 (61.8%) students had compatible anxiety score, while 14 (25.4%) had a compatible score for depression on the HADS questionnaire. There has been a correlation between poor sleep quality, the abuse of technologies before sleep time, and the presence of anxiety or depression.Conclusion The abuse of technology before sleep time reduced the sleep quality in the studied population, besides increasing the symptoms of anxiety and depression.
Keywords: sleep; technology; sleep hygiene; sleep quality; depression; anxiety